"A ray of light amid boundless desolation …": Mandelstam and Pasternak: Reading through the Correspondence. (2nd January 2017) - Ivanova, Natalia
Abstract : Natalia Ivanova traces the relationship of Boris Pasternak and his contemporary, Osip Mandelstam, as recorded in their correspondence and in recollections by others. Despite the differences in their personalities and their poetic fates, their communication and mutual admiration became an increasingly important element in the life of each poet until and even after Mandelstam's death.